Cyst of the canal of Nuck with meconium content as corresponding to meconium orchitis in females: Report of a rare case - Priscila Cardoso Braz Ascar; Antônio Carlos Onofre; Hugo Ítalo Melo Barros; Fernanda Ghilardi Leão (Elsevier, 2023)
Introduction: The cyst of the canal of Nuck, or female hydrocele, occurs due to incomplete closure of the peritoneal-vaginal canal during the antenatal period. During the fetal period, there may be perforation of the intestinal loops with meconium exiting into the abdominal cavity, reaching the peritoneal-vaginal duct, which is still patent. When in contact with the tunica vaginalis around the testicle in boys, the meconium produces an intense inflammatory reaction causing a condition known as meconium orchitis. The corresponding condition in girls is extremely rare, with only two cases having been published so far. Case report: Female infant, 45 days old, presented with an acute condition of hard, painful right inguinal tumor, without other abdominal or intestinal manifestations. She underwent emergency surgery with the hypothesis of an incarcerated inguinal hernia and the intraoperative finding was a rounded tumor with meconium material and an intense inflammatory process in the right inguinal region. When performing inguinal exploration on the left side, material similar to meconium was also found inside the hernial sac, but with a milder inflammatory process. It evolved uneventfully in the postoperative period. Abdominal X-ray performed during outpatient follow-up showed gross and diffuse calcifications in the abdominal cavity. Conclusion: Meconium orchitis, caused by the presence of meconium around the tunica vaginalis in boys, can also occur in girls, manifesting as a cyst of the canal of Nuck with meconium-induced inflammation. Incarcerated inguinal hernia is the main differential diagnosis of this condition and surgical correction should be performed by inguinotomy if there is no associated abdominal manifestation.